Microfabrication of biochip - Balakrishnan, Vishnuvarthan (2011)
Since their discovery, DNA Biochips have been well received and adopted by the research community. The need for high throughput genomic assays is high. Despite vast research in these areas, there is a lack of a simple and reliable methodology. This study investigates one such methodology, aided by vacuum technology to develop PCR-based biochips that enable the analysis of thousands of genes at any one time. Reagents are pre-deposited into rounded wells and sample is loaded onto these wells. The chip is able to conduct high throughput assays. A biochip design is formulated consisting of 100 rounded wells. Advantages of the chip design include low manufacturing cost, high well density, a cover plate for easy pre-deposition of reagents and low cost operation. The chip is also reusable and recyclable. A systematic study of chip design and key parameters was conducted. The key parameters analysed affect effective loading of wells, vacuum conditions inside chip and overall throughput of assay. A standard camera was used to capture fluidic processes within chip. This report will detail the steps taken by the author from the design stage to final testing of biochip.